CONTROLLING THE CHANGING OF MANAGEMENT ACCOUNTING PRACTICES IN THE ENTERPRISE RESOURCES PLANNING ENVIRONMENT - Muhammad Nawawi; Roza Mulyadi; Dabella Yunia (JURNAL MANAJEMEN DAN BISNIS, 2020)
The aims of this research is to give empirical evidence of changes in management accounting practices (MA) by examining the effects of changes in data quality, information quality and management accounting tasks on the efficiency and effectiveness of accounting, and indirectly on change in management accounting after the adoption of an enterprise resource planning (ERP) systems. Empirical analysis of the study used primary data from a survey of 29 manufacturing companies with 102 CFO respondents, accounting managers and business controllers, with a response rate of 28.43%, providing significant support for the proposed model. Structural equation modeling (SEM) approach with testing tools using partial least square (PLS) is used in this research. The linear thing with the results of previous research is the same, it was found that the erp implementation time is the determinant of significant MA changes, while the difference from previous researchers is in the end user, where the company that has adopted the ERP system has just felt a greater MA change when compared to users early on. The results showed that the implementation of global ERP and the use of business intelligence tools (BI) were significantly related to changes in MA practices.